2002
DOI: 10.1046/j.1365-8711.2002.05239.x
|View full text |Cite
|
Sign up to set email alerts
|

Jets in the Fanaroff-Riley class I radio galaxies PKS B1234−723, MRC 1452−517 and PKS B2148−555

Abstract: We present radio observations made with the Australia Telescope Compact Array to study the jets and lobes of three Fanaroff–Riley class I (FR I) radio galaxies: PKS B1234−723, 1452−517 and B2148−555. The total intensity and polarization radio images of the FR I jets are used to determine jet brightness and width variations, magnetic field structure and fractional polarization. The equipartition pressure is determined as a function of distance from the galaxies to probe the intergalactic medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
4
1
Order By: Relevance
“…However, Figure 1 definitely shows diffuse X-ray emission in the field of view (FOV) of this radio source. As reported by Lloyd & Jones (2002), this FR I radio galaxy is the brightest galaxy in Abell cluster A3816, with a largest angular size of 14′.…”
Section: The Case Of Pks B2148-555supporting
confidence: 77%
See 1 more Smart Citation
“…However, Figure 1 definitely shows diffuse X-ray emission in the field of view (FOV) of this radio source. As reported by Lloyd & Jones (2002), this FR I radio galaxy is the brightest galaxy in Abell cluster A3816, with a largest angular size of 14′.…”
Section: The Case Of Pks B2148-555supporting
confidence: 77%
“…We notice the presence, among these 28 sources, of PKS B2148−555, which is one of the 78 G4Jy sources with which, due to their extension, more than one GLEAM component was associated by W20. High-resolution ATCA maps in Lloyd & Jones (2002) show the details of the emission of this relevant radio galaxy.…”
Section: Description Of Our Sample Of Sms4 Sourcesmentioning
confidence: 99%
“…Previous studies of polarisation inside the jets have shown that fractional polarisation tends to increase near the jet edge (e.g. Roberts et al 2013, Lloyd & Jones 2002, i.e. the opposite of what we see here.…”
Section: Bright Knots: Internal Jet Structure?contrasting
confidence: 62%
“…GKW00 made a search through the literature and classified six sources as HYMORS. Four out of six objects from their sample have higher resolution VLBI observations, and they possess core-jet structures with the jet pointing towards the FR I side (Pérez-Torres et al 2004;Beasley et al 2002;Giroletti et al 2004) or two-sided jets (Lloyd & Jones 2002). Two of the objects have been classified as BL Lacs with small viewing angles (Wu et al 2007).…”
Section: Discussionmentioning
confidence: 99%